Decomposition of stochastic power management for wireless base station in smart grid - Kaewpuang, Rakpong (2013)
We propose a stochastic power management (SPM) algorithm for a wireless base station to optimize the power consumption (i.e., minimizing the power cost while meeting wireless traffic demand). This SPM algorithm is developed for a smart grid environment which takes a renewable power source and time-varying power price into account. An optimization model is developed to obtain an optimal solution of the SPM algorithm. This optimization model considers various uncertainties including power price, renewable power, and wireless traffic load. Benders decomposition method is applied to reduce the execution time of obtaining the optimal solution for the SPM algorithm.